Analisis manajemen strategi terhadap pertumbuhan Bank Syariah di Indonesia - Fitriah, Destiana Mahmudatul (Maliki Interdisciplinary Journal, 2025)
This study investigates strategic management that influences the development of Islamic banks in Indonesia, emphasizing the application of sharia principles, digital technology adaptation, and risk management to achieve sustainable growth. Using a descriptive qualitative approach through literature review and case analysis of Bank Syariah Indonesia (BSI), this study examines how strategic management encompasses product innovation (e.g., mudharabah and murabahah), increasing knowledge of Islamic finance, and the use of information technology to improve accessibility and operational efficiency. The findings indicate that effective strategic management can increase Islamic banks' assets to 7% of the national market share, thanks to the encouragement of OJK regulations, collaboration with MSMEs, and digital PR strategies that strengthen the institution's image and customer loyalty. Challenges such as low financial literacy and competition from the conventional sector are addressed through human resource development and financial performance evaluation (ROA, CAR). Overall, Sharia-based strategic management is a crucial element for inclusive growth, with recommendations to integrate AI to achieve the vision of becoming a top 10 Islamic bank in the world by 2030.